Here I am : the story of Tim Hetherington, war photographer - Huffman, Alan. (Grove Press, 2013)
Tim Hetherington (1970-2011), one of the world's most distinguished and dedicated contemporary photojournalists, was killed while covering the Libyan Civil War. This book is a compelling portrait of Hetherington's life and career, exploring the risks, challenges, and thrills of contemporary war photography. Hetherington's dedication to his career led him time after time into war zones, and, unlike some other journalists, he did not pack up after the story had broken. In 2003, after the Liberian civil war ended, Hetherington stayed in the country for three years, helping the United Nations track down human rights criminals. He was profoundly interested in the relationship between young men and war, and the "feedback loop" that images of war create: many young soldiers he encountered seemed to be emulating the images of warriors they'd seen in photos and on television. Hetherington continued his investigation of this theme in Libya, where he travelled to the most dangerous part of the frontline on what would be his final assignment. Only his photographs and video footage survived. This book is a testament to the tireless work of Hetherington and photographers like him, people who risk--and sometimes lose--their lives in order to give a voice to those devastated by conflict.--From publisher description.